The novel functions of chemokines in lung cancer progression - Xiaorui Gong; Xueying Wang; Jing Jin; Zhiqiang Gong (Frontiers in Immunology)
Chemokines are key molecules that regulate immune cell migration and play critical roles in the tumor microenvironment. In lung cancer, chemokine dysregulation is closely linked to tumor progression. They promote immune cell infiltration and interact with tumor cells, enhancing tumor invasiveness and metastatic potential. This review highlights chemokine-mediated mechanisms, focusing on CCR9/CCL25 and CXCL12/CXCR4 axes, which promote tumor growth, metastasis, and immune evasion via PI3K/AKT and MAPK signaling. Elevated expression of these pathways correlates with poor outcomes and aggressive phenotypes. In SCLC, CXCR4 inhibitors show therapeutic promise when combined with chemotherapy or immunotherapy. This review summarizes the prognostic and therapeutic relevance of chemokines in lung cancer progression.